PAZIIM DIGITAL EVIDENCE ANALYSIS APPLICATION ON ANDROID SMARTPHONES WITH A LOGICAL ACQUISITION APPROACH - Dedy Hariyadi; Hendro Wijayanto; Indah Daila Sari (Cyber Security dan Forensik Digital, 2019)
The use of social media in Indonesia has increased very rapidly in 2018 compared to the previous year. This makes a lot of social media made by the children of the nation appear, one of which is Paziim. Socializing on the internet is very easy to leak personal data. There are three aspects that can be utilized on online social networks (OSN) in the disclosure of private data to the public, namely the strength of the relationship (strong or weak), the type of relationship and the characteristics of one's habits. Mobile forensics is needed to analyze digital evidence on social media applications installed on Android smartphones. Indonesia through the National Standardization Agency (BSN) also issued standards related to digital forensics. Standards which are derived from ISO / IEC regulate Security Techniques - Guidelines for the Identification, Collection, Acquisition and Preservation of Digital Evidence. This standardization is known as SNI ISO / IEC 27037: 2014. From the results of cell phone forensic analysis on the Paziim application, the results found the username, coordinates, device models, and operators used by users in SQLite Web_Data and OneSignal.xml files